Start-to-end simulations for bunch compressor and THz SASE FEL at PITZ. Issue 1 (1st January 2023) - Lueangaramwong, A; Li, X; Boonpornprasert, P; Krasilnikov, M; Stephan, F
Abstract: The magnetic bunch compressor was designed as part of a THz accelerator source being developed at the Photo Injector Test facility at DESY in Zeuthen (PITZ) as a prototype for pump-probe experiments at the European XFEL. As an electron bunch is compressed to achieve higher bunch currents for the THz source, the beam dynamics in the bunch compressor was studied by numerical simulations. A start-to-end simulation optimizer including coherent synchrotron radiation (CSR) effects has been developed by combining the use of ASTRA, OCELOT, and GENESIS to support the design of the THz source prototype. In this paper, we present simulation results to explore the possibility of improving the performance of the THz FEL at PITZ by using the developed bunch compressor.